The City and Neighborhood Gang Violence: A Theoretical Approach - Alanezi, Fawaz; Debla, AbdulAli (Al-Adab Journal, 2025)
The current research aimed to shed light on the issue of neighbourhood gang violence in the city, which is increasing day by day. The current research has addressed many important points related to the research topic, as follows: the right to the city, sociology in the face of deviance and crime, violence and crime from a postmodern perspective, the city and gang violence, and the definition of gang violence. Then, the research monitored the factors related to the emergence of neighbourhood gangs.As an attempt by the researchers to explain violence and crime in the city, both the subculture approach and the architectural space approach were explained briefly. Also, at the end of the research, some proposed solutions were presented to confront the phenomenon of neighbourhood gangs, and a future vision for life in the city was presented so that we can obtain the right to live in a suitable, positive, stimulating and clean city... for us and for our children after us.